2007
DOI: 10.1007/s00421-007-0540-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of exercise intensity on time spent at high percentage of maximal oxygen uptake during an intermittent session in young endurance-trained athletes

Abstract: The purpose of this study was to compare, during a 30s intermittent exercise (IE), the effects of exercise intensity on time spent above 90% VO2max(t90VO2max) and time spent above 95% VO2max(t95VO2max) in young endurance trained athletes. We hypothesized that during a 30sIE, an increase in exercise intensity would allow an increase in t90VO2max and t95VO2max due to a decrease in time to achieve 90% or 95% of VO2max. Nine endurance-trained male adolescents took part in three field tests. After determination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
2
3

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 39 publications
2
31
2
3
Order By: Relevance
“…They found a longer time to exhaustion when recovery was passive (745 § 171 vs. 445 § 79 s, p < 0.001). Thevenet et al (2007) reported similar results following a HIIE session involving intermittent runs of 30 s at 105% of MAS interspersed with 30 s of either active (50% MAS) or passive (0% MAS) recovery (2,145 § 829 vs. 1,072 § 388 s, p < 0.01). Our results are therefore in agreement with the existing literature on healthy subjects.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…They found a longer time to exhaustion when recovery was passive (745 § 171 vs. 445 § 79 s, p < 0.001). Thevenet et al (2007) reported similar results following a HIIE session involving intermittent runs of 30 s at 105% of MAS interspersed with 30 s of either active (50% MAS) or passive (0% MAS) recovery (2,145 § 829 vs. 1,072 § 388 s, p < 0.01). Our results are therefore in agreement with the existing literature on healthy subjects.…”
Section: Discussionmentioning
confidence: 55%
“…First, the acute cardiopulmonary responses of these protocols were not studied prior to their implementation into training programs. In healthy subjects, manipulating exercise/recovery intensity has been shown to alter time to exhaustion and time spent at a high percentage of VO 2 independently of bout duration (Billat 2001;Dupont et al 2003a;Thevenet et al 2007). In the absence of this speciWc information, it is diYcult to determine whether the HIT protocols used by Rognmo et al (2004), Warburton et al (2005), andWisloV et al (2007) induced a cardiovascular response that was optimal for improving VO 2max .…”
Section: Introductionmentioning
confidence: 99%
“…Nossos resultados demonstraram um efeito da intensidade no Tlim (ver tabela 1), corroborando com outros estudos, que também encontraram um maior tempo de exercício e quantidade de séries executadas quando a intensidade era relativamente menor (DUPONT et al, 2002;THEVENET et al, 2007). Esta resposta poderia ser explicada pela menor contribuição do sistema anaeróbio na ressíntese do ATP (ROZENEK et al, 2007), o que provavelmente diminuiria a produção e acúmulo de metabólitos responsáveis pela instalação da fadiga e conseqüente interrupção do exercício (ver tabela 1).…”
Section: Sujeitosunclassified
“…Contudo, a razão esforço:recuperação de 2:1 apresentou melhores resultados para t95VO 2 max do que exercícios com razão esforço:pausa de 1:1 . Assim, a utilização de 30s de esforço intercalados por 15s de recuperação, pode ser um ótimo estímulo para aumentar o tempo mantido em altos percentuais do VO 2 max, visto que, 30s de esforço é suficiente para o VO 2 alcançar o seu valor máximo após algumas séries de exercício (THEVENET et al, 2007). Além disso, um menor tempo de recuperação (15s) permite manter o VO 2 ainda elevado ao final da recuperação, fazendo com que o tempo para alcançar novamente o VO 2 max seja reduzido durante a série subseqüente (DUPONT et al, 2002).…”
unclassified
“…The prescription of HIIT is almost infinitely variable due to the many possible combinations of exercise mode, exercise intensity, duration and number of intervals performed, and the durations and nature of the recovery periods between exercise bouts [245] . However, the common characteristics of HIIT are: (1) it involves repeated short-to-long bouts of rather high-intensity exercise interspersed with recovery periods [27] ; (2) the intensity is between 80-100% peak heart rate [26] (compared to ≥ 100% V O2max, which is classified as 'sprint-interval training' [26] ); and (3) the intensity of the relief intervals are characterised in alignment with the intensity of the work intervals, that is, higher intensity relief intervals are prescribed for lower intensity work intervals [246] and lower intensity relief intervals are prescribed for work intervals of higher intensities and durations [247][248][249] . The aim of this section is to 123 review the physiological and performance adaptations to HIIT in endurance-trained athletes.…”
Section: High-intensity Interval Training (Hiit) In Trained Endurancementioning
confidence: 99%